V.2 - Karim, Fazal (Delhi, 2006)
This book define on Judicial Review, contextually considered. the context is a written Constitution. The purpose of judicial review was ' to enforce the legal limits of public and in particular executive-power' the book contains, beside a fairly exhaustive study of the Constitutional concept of 'Judicial Power' a treatment of the constitutional concept of the 'Legislative Power' and the 'Executive Power' of the state.
Volume 2 Judicial review of public actions
Keywords: Judicial review